LAPAROSCOPIC THROMBECTOMY WITH RADICAL NEPHRECTOMY FOR RENAL CELL CARCINOMA WITH INFERIOR VENA CAVA THROMBUS - D. V. Perlin; V. P. Zipunnikov; I. N. Dymkov; A. O. Shmanev; M. B. Popova (Вестник урологии, 2016)
Laparoscopic radical nephrectomy (LRN) is presently viewed as the standard treatment for localized renal cancer. However, 5–10% of renal cell carcinoma is associated with the development of the tumor thrombus. The works of few authors have demonstrated the feasibility of laparoscopic radical nephrectomy in patients with tumor thrombus in renal vein. We describe the method and report our own experience of LRN with thrombectomy from the inferior vena cava. Two patients with renal masses with infrahepatic tumor thrombus underwent right-sided radical nephrectomy and thrombectomy. After clipping the right renal artery, we dissected the IVC above and below the level of the thrombus and introduced the vessel loops. In addition to that we mobilized the left renal vein and clipped the right gonadal vein. After occluding the IVC and the left renal vein with a vessel loops or a laparoscopic Satinsky vascular clamp, we made an incision the IVC wall, extracted the thrombus and excised the ostium of right renal vein. The defect in the IVC was closed with running sutures. Laparoscopic RN and thrombectomy were successfully performed in all the patients without conversion to open surgery. With a mean follow-up 8–20 months all patients have no signs of local recurrences or distant metastases. Laparoscopic RN with IVC thrombectomy in selected RCC-patients with differential extensions of tumor thrombus is a safe and feasible procedure. Additional studies are needed to examine the advantages of this approach.